(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to evaluate the self-care knowledge of patients with peptic ulcers undergoing inpatient treatment in the Gastroenterology Department of Nam Dinh Provincial General Hospital. Method: A cross-sectional descriptive study was conducted using a convenience sampling method and a self-administered questionnaire to describe the patients’ knowledge. Results: More male patients were treated for peptic ulcers than female patients, with the average age of the patients being 54.3 ± 5 years. The most common cause of peptic ulcers identified by patients was the use of painkillers and anti-inflammatory drugs, which accounted for 36%. Forty percent of patients recognized that the clear symptom of peptic ulcers in the gastrointestinal bleeding stage was vomiting blood and having black stools. Twenty-eight percent of patients were aware of gastrointestinal bleeding as a complication, and 26% knew about the complication of pyloric stenosis. Only 10% of patients had correct knowledge about the diet during the bleeding stage, while 18% had correct knowledge about the diet during the hemostasis stage. Twenty-four percent of patients knew which foods should be avoided for peptic ulcers. Regarding rest regimes, more than 50% of patients had correct knowledge, but 58% answered incorrectly about the follow-up schedule. Conclusion: The self-care knowledge of patients with peptic ulcers was limited, with 62% of patients having poor knowledge, 22% having average knowledge, and 16% having good knowledge.